2016
DOI: 10.1515/cjf-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the adoption of improved aquaculture technologies among fish farmers in Lagos State, Nigeria

Abstract: The study assessed the adoption of improved aquaculture technologies among fish farmers in Lagos State, Nigeria. A total of 90 fish farmers were sampled through the multistage sampling technique. A validated and pretested interview schedule was used to obtain primary information from the fish farmers. Obtained data were analyzed using descriptive and inferential statistics. Results obtained revealed that more than half and about one-third of the fish farmers sourced credit facilities from cooperative societies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
(8 reference statements)
5
12
2
Order By: Relevance
“…Socio-economic characteristics of farmers Farmers' adoption of SAMP was highly influenced by socio-economic status which changes over time (Olaoye et al 2016). Study found that the mean age of farmers was 38 years while their level of education was 8 years (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Socio-economic characteristics of farmers Farmers' adoption of SAMP was highly influenced by socio-economic status which changes over time (Olaoye et al 2016). Study found that the mean age of farmers was 38 years while their level of education was 8 years (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Women's role is similarly masked by ownership of land and other production facilities frequently being formally or informally held by male household members (Kruijssen et al 2018). The low uptake of aquaculture among women and especially the youth is a threat to the social sustainability of aquaculture (Obwanga and Lewo 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still relatively few attempts to make predictions about adoption outcomes using these factors (Kuehne et al 2017). Moreover, only a few studies have analyzed the factors influencing fish farmer's perceptions, attitudes, and behavior (Ndah et al 2011;Wandji et al 2012;Olaoye et al 2016). In this study, we present and apply a modified analytical framework, showing the linkages and interaction between extrinsic variables and intrinsic variables in the decision-making process of technology adoption (Fig.…”
Section: Analytical Framework For Technology Adoptionmentioning
confidence: 99%
“…The state has a 3,577 km 2 . Size, the maritime shoreline of 180 km with 30% of the total land mass made up of a network of water bodies (Olaoye et al, 2016). The state lies approximately within longitude 2°42'E and 3°42'E and stretches between latitude 6°22'N and 6°42'N.…”
Section: Methodsmentioning
confidence: 99%